Context‐dependent interactions between pathogens and a mutualist affect pathogen fitness and mutualist benefits to hosts. Issue 12 (9th November 2018) - Marchetto, Katherine M.; Power, Alison G.
Abstract: Plants and animals host many microbial symbionts, including both pathogens and mutualists. However, most experimental studies include only one symbiont, and few examine interactions of more than two microbes with their host. Here, we examined whether coinfection with two pathogens causes a synergistic reduction in the benefits that hosts receive from a microbial mutualist. We also measured the effects of a microbial mutualist on the within‐ and between‐host competition between coinfecting pathogens. We manipulated the presence of Clover yellow vein virus (ClYVV), Bean common mosaic virus (BCMV), rhizobia bacteria, and nitrogen fertilizer in common beans ( Phaseolus vulgaris ). We found asymmetric, context‐dependent interactions among the three microbial symbionts and their host. Coinfection with both viruses led to greater than additive negative effects on the amount of nitrogen that plants received from rhizobia. Rhizobia colonization decreased immune signaling in singly infected plants, but not in coinfected plants. Compared to single ClYVV infection, ClYVV reached higher concentrations within hosts coinfected with BCMV, but only in the presence of rhizobia. Coinfection increased BCMV vertical transmission rates for plants without supplemental nitrogen, but overall vertical transmission opportunities were not affected due to reduced seed production. Examining interactions between multiple microbes sharing a host can reveal important insights about nutrient cycling, disease severity, and pathogen epidemiology.